Improving Science Learning Outcomes with Hands-On-Minds-On Learning Model on The Third Graders Of Elementary School - Ike Nilawati Rohaenah; Ngadiyem; Dinan Hasbudin; Fauzi; Prahasinta Dewie (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
Hands-On-Minds-On as a learning approach involves activities and direct experiences with natural environment or educational experiences that actively involve students in manipulating objects to gain knowledge or understanding to reform and improve science learning outcomes by using Hands-On-Minds-On learning model for third grade students at SDN Tengah 07 Pagi. The total number is 42 students, 20 students were taken as sample population. Based on the result of the first pre-cycle research, it was found that 13 students did not reach the Minimum Completeness Criteria (KKM), and students who obtained above the Minimum Completeness Criteria (KKM) were 7 students. From the result of the pre-cycle research, it was found that the value of Class III A is still relatively low with an average score of 60.75. Whereas, the Minimum Completeness Criteria (KKM) for science subject is 65. In the second cycle, teacher includes more learning media, makes classroom situation more enjoyable and provides many opportunities for students to be active in learning process. Finally, the learning outcomes also increase from the average students’ learning outcomes of 78.50 to 85.25. Therefore, it can be concluded that the research cycle I and cycle II can improve the students’ learning outcome on science learning in class III A by using the Hands-On-Minds-On learning model. Thus, the research ends in the second cycle